Legal violence: the struggles of Thai women in Thai massage businesses - Kantachote, Krittiya (Frontiers in Sociology, 2024)
Prior studies of legal violence concerning minority groups in the United States are often linked to Immigration Law. Drawing primarily from 30 interviews with Thai massage business owners in Los Angeles, this article reveals how the implementation of local and federal regulations and laws regarding massage businesses constitutes legal violence. Using Crenshaw’s structural, political, and representational intersectionality, this article demonstrates how Thai women’s race, ethnicity, and gender affect their experiences in countering the state regulations. The analysis focuses on two interrelated areas of Thai massage business owners’ and Thai massage therapists’ lives—the strict government surveillance of Thai massage business operations and the enforcement of professional certification. This legal violence toward Thai massage owners and massage therapists is rooted in a legal system that aims to protect consumers. Nevertheless, the effect of legal violence is not limited to undocumented Thai immigrants but also affects Thai American citizens and legal permanent residents.